Investigating Factors Affect Perceived Value And E-Word Of Mouth (E-WOM) In Choosing Islamic Digital Banks - Luthfiyah, Afifatunisa; Wulandari, Nuri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2024)
The Covid-19 pandemic has sped up the need for digitalization in doing daily activities including banking. Thus, banks is now in competition to give the best digital platform to serve their customers. One of the most effective form of promotion to introduce a new services is word of mouth. This study aims to investigate the effect of E-word of mouth (E-WOM) on customer decisions to choose an Islamic Bank: A Case Study of Indonesia’s Islamic Digital Banks. This research includes survey research by taking samples and using questionnaires as the main data. The study targetted 130 customers who have active accounts in the form of savings or time deposits. Primary data processing by factor analysis by testing the research model and the hypothesis of the relationship between variables, this processing uses smart PLS statistical software with the Structural Equation Modeling method with Partial Least Squares. The results of the analysis show that religious motivation and service quality have a positive effect on consumer ratings, where consumer ratings and service quality have a positive effect on E-word of mouth while convenience has no positive effect on consumer ratings and E-word of mouth on respondents. The current study contributes novelty to adjust the existing model with Islamic Digital Bank (IDB).